Arthroscopic management of tibial eminence fracture: a review of treatment outcome - S., Shreekantha K.; N., Gowthamapradhaban; Malik, Deepak; ., Mahendranath (International Journal of Research in Orthopaedics, 2021)
In this study outcomes of arthroscopic management of tibial eminence fracture have been described. We conducted a study of 15 patients of ACL avulsion fractures especially Meyer and Mckeever type II and III treated arthroscopically by pull through sutures. Outcome measures were assessed through International Knee Documentation Committee (IKDC) form, Tenger Activity scale and Lysholm knee score. The study group consisted of 15 patients who met the inclusion criteria, of which 9 were male and 6 were female. The range of patient age consisted of 13-37 years and the average patient age was 20.6 years. The average male age was 22.11 years and the average female age was 18.33 years. The fracture classification showed 7 being type II while 8 were type III. Tegner Activity level at follow up ranged from 5-8 and the mean score was 6.4. On follow-up evaluation, the mean Lysholm score was 92.8 (ranging from 76-100). 6 patients who had inter-meniscal interposition was retracted or resected showed no difference in functional outcome. We found that displaced tibial eminence fractures could be successfully treated using arthroscopic pull through sutures, with most patients returning to their previous activity level. Complications were avoided by anatomic reduction of fracture fragments and early post-operative rehabilitation.